2015
DOI: 10.1097/adt.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Training Needs of New England HIV Care and Addiction Treatment Providers

Abstract: Objectives Unhealthy alcohol use is common among HIV-infected patients and contributes to co-morbidities, cognitive decline, unprotected sex, and poor medication adherence. Studies consistently show missed opportunities to address unhealthy alcohol use as part of care. Although treatment of other drug use has been integrated into HIV care in some settings, more information is needed regarding provider attitudes regarding the need for integration of alcohol treatment and HIV care. Methods We surveyed 119 HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Our results are similar to those recently reported by Montague and colleagues (Montague et al, 2015). In their study, HIV providers (N=159) also reported moderate to high levels of confidence in their abilities to assess and monitor patients with heavy/hazardous drinking patterns, and lower confidence in their ability to effectively manage alcohol treatment needs on-site in the HIV clinic.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are similar to those recently reported by Montague and colleagues (Montague et al, 2015). In their study, HIV providers (N=159) also reported moderate to high levels of confidence in their abilities to assess and monitor patients with heavy/hazardous drinking patterns, and lower confidence in their ability to effectively manage alcohol treatment needs on-site in the HIV clinic.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, alcohol pharmacotherapy is available through the VA in addition to other addiction treatment services [6769]. These services may be more robust than those available in some non-VA HIV treatment settings [16]. Participants could be referred for additional services as deemed appropriate by their providers.…”
Section: Methodsmentioning
confidence: 99%
“…However, again, the availability of non-VA communitybased specialty addictions treatment for AUD in rural areas is unclear. 59 In addition, AUD medications have been shown to be as effective as specialty addictions treatment when prescribed along with ongoing medical management, [67][68][69] and thus may be a viable option for provision in primary care settings.…”
Section: Discussionmentioning
confidence: 99%
“…10 Further, while barriers indicate a need for more training about the importance of offering alcohol-related care to PLWH and the efficacy of AUD medications, HIV providers report ambivalence about receiving training in treatment of substance use disorders. 68 Primary care providers also report barriers to prescribing AUD medications, including a lack of time for training and a lack of support in managing AUD care. 54 There also may be contraindications for use of some AUD medications among HIV patients (such as naltrexone among patients with hepatic problems).…”
Section: Discussionmentioning
confidence: 99%